Periodesasi dan Perkembangan Dinasti Umayyah - Muhammad Luthfi Anam Khoirudin; Kholid Mawardi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
This study describes the Development of Islam in the Umayyad Period. The focus of this research is to find out the history of the establishment of the Umayyads, Islamic civilization during the Umayyad period, and the reasons for its decline and the fall of the Umayyads. The result is the Umayyad dynasty is taken from the name Umayyah Ibn 'Abdi Shams Ibn 'Abdi Manaf, this dynasty was actually initiated since the leadership of caliph Uthman bin Affan but only later successfully declared and gained recognition of sovereignty by all the people after the caliph Ali was killed and Hasan ibn Ali who was appointed by the people the Muslims in Iraq handed over their power to Muawiyah after doing so negotiations and agreements. The unity of the Muslim ummah in one leadership at that time was called the jama'ah year ('Am al Jama'ah) 41 H (661 M). And the decline and destruction of the Umayyad dynasty was caused by many factors, among them are: power struggles between royal families, prolonged conflict with the Shia and Khawarij opposition groups, ethnic conflict between North Arab tribes and South Arab tribes, the incompetence of the caliphs in leading the government and the tendencies of those who live luxury, overthrow by the Bani Abbas fully supported by the Bani Hashim, the Shia, and the Mawali group.